Oxygenerator remote control system - JI GUIGONG; KONG ZHIGUO (2018)
The utility model discloses an oxygenerator remote control system. It includes oxygenerator host computer and the host computer control module who is connected with the oxygenerator main part, and host computer control module connects the remote control unit, is connected with pressure sensor, oxygen concentration sensor and flow sensor on the oxygenerator host computer, and the remote control unit still is connected with the audio frequency module that can carry out audio playback, and the audio frequency module is connected with the speaker. After the structure of the utility model is adopted, can directly operate at the scene, can also carry out remote operation through the remote control unit, can also be through the remote control unit to pressure, detection and control is carried outto oxygen concentration and flow information, the controllability is greatly improved, its structural design not only makes its degree of automation improve greatly, and long -range operation has improved the convenience of